Sex differences in the association between body mass index and total hip or knee joint replacement resulting from osteoarthritis. Issue 4 (26th May 2008) - Franklin, J; Ingvarsson, T; Englund, M; Lohmander, L S
Abstract : Objective: To examine the association between body mass index (BMI) and osteoarthritis (OA) leading to total hip (THR) or knee (TKR) joint replacement. Methods: Case–control study design. All patients still living in Iceland who had had a THR or TKR resulting from OA before the end of 2002 were invited to participate. First-degree relatives of participating patients served as controls. A total of 1473 patients (872 women) and 1103 controls (599 women), all born between 1910 and 1939 and who had answered a questionnaire including questions about height and weight, were analysed. A randomly selected sample, representative of the Icelandic population, was used as a secondary control group. Results: The OR, adjusted for age, occupation and presence of hand OA, for having a THR was 1.1 (95% CI 0.9 to 1.5) for overweight men and 1.7 (95% CI 1.0 to 2.9) for obese men. The OR for having a TKR was 1.7 (95% CI 1.1 to 2.6) for overweight men and 5.3 (95% CI 2.8 to 10.1) for obese men. The OR for having a THR was 1.0 (95% CI 0.8 to 1.3) for overweight women and 1.0 (95% CI 0.6 to 1.5) for obese women. The OR for having a TKR was 1.6 (95% CI 1.1 to 2.2) for overweight women and 4.0 (95% CI 2.6 to 6.1) for obese women. Conclusion: This study supports a positive association between high BMI and TKR in both sexes, but for THR the association with BMI seems to be weaker, and possibly negligible for women.